Effect of light spectra on stem cutting rooting and lavender growth - Diego Alves Peçanha; José Ángel Moro Peña; Marta Simone Mendonça Freitas; Yasmina Chourak; Miguel Urrestarazu (Acta Scientiarum: Agronomy, 2023)
French lavender (Lavandula dentata L.) is of great ornamental, medicinal, and aromatic interest. It is generally propagated vegetatively using stem cuttings. When using artificial lighting, a specific light composition can modify the entire plant phenology and is a factor that can be managed in controlled conditions. This study evaluated the rooting of stem cuttings and growth of lavender under four spectral LED lights. The LED lights used were: T0 (white LED, Roblan®), T1 (AP67 Milky, Valoya®), T2 (NS1, Valoya®), and T3 (AP673L Milky, Valoya®). The first phase evaluated the rooting of stem cuttings and initial development. The plants were then transferred to plastic pots to evaluate plant growth. In both rooting and growing phases, the plant morphological characteristics and water and light efficiencies were evaluated. Nutrient-uptake efficiencies were also evaluated after the growing phase. It was observed that cuttings rooted under the influence of T1 showed greater height. After the growing phase, plants under T3 showed better results in electricity use efficiency, water use efficiency, and nutrient-uptake efficiency and less nitrate leaching. They also presented more uniform growth with a compact canopy. Thus, T1 was better for the stem cuttings rooting phase, while T3 was better for growth and energy efficiency.